Pengaruh Fenomena Slang Digital Brainrot terhadap Pola Komunikasi di Kalangan Gen Z - Baginda Muhammad Wahyu Keyfa; Lukman (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the impact of digital slang brainrot phenomenon on Generation Z's communication patterns in Indonesia. Using a descriptive quantitative approach through a survey of 109 respondents, the research analyzes the use of terms like rizz, gyatt, and sigma in daily interactions. Results indicate TikTok as the dominant platform (59.5%) for brainrot content dissemination, with 50.5% of respondents acknowledging intergenerational comprehension gaps. Employing Uses and Gratifications Theory and Mass Communication Theory, the study explains how brainrot serves both as an identity expression tool and entertainment source (82%), despite 64% of respondents recognizing its negative cognitive impacts, particularly reduced focus. Key findings reveal that brainrot language has established absurdist and expressive communication patterns among Gen Z while simultaneously creating communication barriers with older generations. The research recommends enhancing media literacy and adopting educational approaches to maximize benefits while mitigating the psychological risks associated with this phenomenon.